Recombinant Human SCARB2 Expressed in Escherichia coli and its Potential in Enterovirus 71 Blockage - Vo-Nguyen, Hai-Vy (Iran J Sci Technol Trans A Sci, 2021)
Hand, foot and mouth disease is a common viral infectious disease caused by enteroviruses, including coxsackie A16 (CVA16) and enterovirus 71 (EV71). HFMD can cause severe symptoms in children which can be fatal. Human scavenger receptor class B member 2 (SCARB2) is a cellular receptor for EV71 and CVA16, providing a potential approach for preventing EV71 infection and transmission. In this present study, we constructed and assessed the potential of recombinant SCARB2, using E. coli expression system. To generate this construct, scarb2 gene was cloned into pET22b vector and expressed in E. coli BL21 (DE3). The expression of SCARB2 was induced by 0.1 mM IPTG and analyzed using SDS-PAGE, followed by Western blot. Expressed SCARB2 was in inclusion bodies and refolded to obtain the soluble form with recovery efficacy of 100%. This recombinant protein was then validated for binding with EV71 via indirect ELISA in two different pHs (7.4 and 5.5), which partially revealed the mechanism of virus–receptor interaction. These results envisaged potential applications for utilizing recombinant SCARB2 in preventing the virus transmission.